2022
DOI: 10.3390/ma15165551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mass on the Dynamic Characteristics of Single- and Double-Layered Graphene-Based Nano Resonators

Abstract: Graphene has been widely and extensively used in mass sensing applications. The present study focused on exploring the use of single-layer graphene (SLG) and double-layer graphene (DLG) as sensing devices. The dynamic analysis of SLG and DLG with different boundary conditions (BDs) and length was executed using the atomistic finite element method (AFEM). SLG and DLG sheets were modelled and considered as a space–frame structure similar to a 3D beam. Spring elements (Combin14) were used to identify the interlay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Graphene is known for its exceptional strength, especially in terms of its tensile strength. The theoretical tensile strength of graphene is extremely high, estimated to be around 130 GPa [28]. Experimental studies have reported tensile strengths for graphene ranging from 20 to 130 GPa [29], the chirality of graphene is typically described using two integers, (n, m), which represent the vector components of a translation that describes how a graphene sheet is rolled into a tube to form a carbon nanotube [30].…”
Section: Inter Atomic Modelling Of Slgmentioning
confidence: 99%
“…Graphene is known for its exceptional strength, especially in terms of its tensile strength. The theoretical tensile strength of graphene is extremely high, estimated to be around 130 GPa [28]. Experimental studies have reported tensile strengths for graphene ranging from 20 to 130 GPa [29], the chirality of graphene is typically described using two integers, (n, m), which represent the vector components of a translation that describes how a graphene sheet is rolled into a tube to form a carbon nanotube [30].…”
Section: Inter Atomic Modelling Of Slgmentioning
confidence: 99%
“…The capacity of fuzzy logic to manage uncertainty makes it a viable tool for improving energy management techniques in the presence of changeable renewable supplies. [26][27][28][29][30] Performance evaluation and comparative studies have been conducted in the literature to assess the effectiveness of energy management systems based on fuzzy logic. These assessments often include indicators such as grid stability, dependability, and overall efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The integration of AI is crucial because to its potential advantages, which include enhanced efficiency and competitiveness. However, the same technical advancements that make these advantages possible also make a rigorous assessment of the hazards related to AI-driven systems necessary [24]- [28]. The need for thorough security measures is highlighted by the changing threat environment, which is typified by cyberattacks and data breaches.…”
Section: Review Of Literaturementioning
confidence: 99%